Liberal–local peacebuilding in Solomon Islands and Bougainville: advancing a gender-just peace?. (1st November 2018) - George, Nicole
Abstract: The 'local turn' in peacebuilding has been inspired by the idea that post-conflict order is made more just, representative and legitimate when there is greater recognition and incorporation of local sites of authority. However, the gendered visions of security that may be projected from these spheres have often escaped critical attention. This oversight continues despite growing feminist interest in understanding both the contributions that women can make to the durability of conflict settlement processes and the obstacles that often prevent those contributions from progressing. In this article, I examine the frictional encounters that occur between the local and the liberal in peacebuilding and focus particularly on what this means for women. I argue that a focus on vernacular security provides a productive analytical lens for answering this question and for building understanding of where and how women are advantaged and disadvantaged by projects of post-conflict transition. My findings demonstrate how the security vernaculars that are generated in liberal–local peacebuilding produce scenarios that are often contradictory for women and can be enabling and constraining in different contexts. The discussion draws from recent research findings on the gendered impacts of peacebuilding and post-conflict restoration in Bougainville, an autonomous territory of Papua New Guinea, and Solomon Islands.